Research on the Status Quo and Dilemma of Minors' Personal Information Protection: -- From the Perspective of Guardian Consent System - Lou, Kejia; Wu, Jiale; Zhou , Ziyu (Transactions on Social Science, Education and Humanities Research, 2024)
With the rapid development of mobile Internet, minors' personal information is inevitably collected and processed by various information processors. Due to the characteristics of immature mental development and weak risk prediction ability of minors, it is difficult to effectively protect their personal information security. Although China's "Personal Information Protection Law" makes provisions on the protection of minors' personal information, there are still some problems such as "one-size-fits-all" age limit and imperfect guardian consent system. This paper will test the current hundreds of various types of apps, conduct a questionnaire survey on the protection of personal information of minors and their guardians, analyze the current dilemma of the protection of personal information of minors at the social level, propose countermeasures according to the symptoms, and explore more targeted ways to protect the rights and interests of minors' personal information. Escort the physical and mental healthy development of minors under the background of the information age.